Comparative Study of Phytolacca Species Through Morphological, Chloroplast Genome, and Phylogenetic Analysis - Sumin Jeong; Yeseul Kim; Heewon Ji; Jun-Ho Song; Inkyu Park (Applied Sciences)
Phytolacca acinosa Roxb. and P. americana L. are recognized as the primary sources of Phytolaccae Radix, which is traditionally utilized for various medicinal purposes. However, because of their potent toxicity, it is essential to distinguish these species. This study has aimed to clarify the classification of Phytolacca species based on their morphology and genetic differences. The chloroplast genome of P. acinosa was sequenced and comparative analyses were conducted to identify the regions of variation and nucleotide diversity among the species. The results revealed that P. acinosa shares more sequence similarity with other Phytolacca species than with P. americana. Additionally, the dN/dS analysis showed that the ndhH gene of P. americana had a value of 1.0871, indicating positive selection. The phylogenetic tree, supported by strong bootstrap values and posterior probabilities, confirmed that P. acinosa and P. americana formed distinct clusters. Furthermore, the estimated divergence time between P. acinosa and P. americana was approximately 15.07 million years ago, indicating that they diverged earlier than P. insularis, P. polyandra, P. japonica, and P. latbenia. These findings indicated that P. acinosa and P. americana are phylogenetically distinct species, highlighting the need for accurate species identification and taxonomic reassessment to ensure the safe use of these toxic medicinal plants.